2017
DOI: 10.1186/s13011-017-0112-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical pain is common and associated with nonmedical prescription opioid use among people who inject drugs

Abstract: BackgroundPeople who inject drugs (PWID) often have poor health and lack access to health care. The aim of this study was to examine whether PWID engage in self-treatment through nonmedical prescription opioid use (NMPOU). We describe the prevalence and features of self-reported physical pain and its association with NMPOU.MethodsPWID (N = 702) in San Francisco, California (age 18+) were recruited to complete interviewer administered surveys between 2011 and 2013. Multivariate logistic regression analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…The high prevalence of pain in our study was not surprising, given that PWID are vulnerable to skin infections, venous ulcers, co‐morbidities, unstable housing and poverty, which are directly causal or known risk factors for pain . Findings from the present study showed a similar prevalence of pain among PWID who have been exposed to HCV compared to available literature .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The high prevalence of pain in our study was not surprising, given that PWID are vulnerable to skin infections, venous ulcers, co‐morbidities, unstable housing and poverty, which are directly causal or known risk factors for pain . Findings from the present study showed a similar prevalence of pain among PWID who have been exposed to HCV compared to available literature .…”
Section: Discussionsupporting
confidence: 73%
“…Although the mechanisms and pathways are not clearly known, inflammatory cytokines in HCV are theorised to play a role . Additionally, chronic pain is a common condition among PWID, occurring in one‐third to half of the population . These individuals are often exposed to soft tissue infections due to injections, as well as poor health and nutrition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overdose crisis is also the culmination of shifting opioid usage trends (i.e., from initiating opioids via heroin to initiating with pharmaceutical opioids [4]) that can be traced back, in part, to the over-prescription of pharmaceutical opioids for chronic non-cancer pain [5]. Despite this trend of liberal opioid prescribing, certain marginalized populations experiencing high rates of pain, including people who use drugs (PWUD), lack access to adequate pain management through the healthcare system [6,7]. Under-or untreated pain in this population can promote higher-risk substance use, as patients may seek illicit opioids (i.e., unregulated heroin or counterfeit/diverted pharmaceutical opioids) to manage pain [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this trend of liberal opioid prescribing, certain marginalized populations experiencing high rates of pain, including people who use drugs (PWUD), lack access to adequate pain management through the healthcare system [6,7]. Under-or untreated pain in this population can promote higher-risk substance use, as patients may seek illicit opioids (i.e., unregulated heroin or counterfeit/diverted pharmaceutical opioids) to manage pain [6,7]. In Vancouver, this practice poses a particularly high risk of accidental overdose, as estimates show that almost 90% of drugs sold as heroin are contaminated with synthetic opioids, such as fentanyl [8].…”
Section: Introductionmentioning
confidence: 99%